Green Solvents II Properties and Applications of Ionic Liquids - Mohammad, Ali.; Inamuddin, Dr.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
The conventional solvents used in chemical, pharmaceutical, biomedical and separation processes represent a great challenge to green chemistry because of their toxicity and flammability. Since the beginning of (3z(Bthe 12 Principles of Green Chemistry(3y (Bin 1998, a general effort has been made to replace conventional solvents with environmentally benign substitutes. Water has been the most popular choice so far, followed by ionic liquids, surfactant, supercritical fluids, fluorous solvents, liquid polymers, bio-solvents and switchable solvent systems. Green Solvents Volume I and II provides a throughout overview of the different types of solvents and discusses their extensive applications in fields such as extraction, organic synthesis, biocatalytic processes, production of fine chemicals, removal of hydrogen sulphide, biochemical transformations, composite material, energy storage devices and polymers. These volumes are written by leading international experts and cover all possible aspects of green solvents$1 (Bproperties and applications available in today$1 (Bs literature. Green Solvents Volume I and II is an invaluable guide to scientists, R&D industrial specialists, researchers, upper-level undergraduates and graduate students, Ph.D. scholars, college and university professors working in the field of chemistry and biochemistry.s
From the Contents: Ionic Liquids as Green Solvents: Progress and Prospects -- Ionic Liquids as Green Solvents for Alkylation and Acylation -- Ionic Liquids as Green Solvents for Glycosylation Reactions -- Ionic Liquid Crystals -- Application of Ionic Liquids in Extraction and Separation of Metals -- Potential for Hydrogen Sulfide Removal Using Ionic Liquid Solvents -- Biocatalytic Reactions in Ionic Liquid Media -- Ionic Liquids/Supercritical Carbon Dioxide as Advantageous Biphasic Systems in Enzymatic Synthesis -- Ionic Liquids as Lubricants.
Keywords: Chemistry; Chemistry, Organic; Chemical engineering; Environmental chemistry; Chemistry; Industrial Chemistry/Chemical Engineering; Environmental Chemistry; Organic Chemistry